Parent–child relationship quality and adolescent health: Testing the differential susceptibility and diathesis‐stress hypotheses in African American youths. Issue 1 (2nd September 2021) - Shakiba, Nila; Gao, Mengyu (Miranda); Conradt, Elisabeth; Terrell, Sarah; Lester, Barry M.
Abstract: This study tested two competing models of differential susceptibility and diathesis‐stress in a prospective longitudinal study of African American youths ( N  = 935). It examined whether individual variations in the functioning of the hypothalamic–pituitary–adrenocortical axis at age 11 interact with middle childhood parent–child relationship quality to predict mental and physical health problems in adolescence (ages 11–15 years old). Adolescent boys with lower levels of cortisol reactivity to laboratory challenges had the highest levels of internalizing problems if they experienced a high conflictual relationship with their parents. Equally low‐reactive boys, however, reported the lowest number of physical illnesses if their relationship with their parents was characterized by high levels of intimacy and support.